(untitled) (Brazilian Journal of Radiation Sciences, 2021)
Approximately 75% of breast cancer cells express estrogen receptor positive, being the second leading cause of cancer death among women worldwide with an incidence of 25% per year. 16α-[18F]-fluoro-17β-estradiol, FES-18F, is a radiopharmaceutical that binds to estrogen receptors enabling the acquisition of molecular images for non-invasive diagnosis of primary and metastatic breast cancer using PET-CT. The objective of this work was to study the synthesis of FES-18F in the GE TRACERlab® MXFDG module, using the chemical kit and the ABX® disposable cassette, and to determine the process yield and the analytical parameters to be used in the routine production of this radiopharmaceutical. Automated synthesis occurs in 75 minutes and includes percolation of [18F-] fluoride into an anion exchange cartridge, cartridge elution, 3-step azeotropic drying, labeling using precursor 3-methoxymethyl-16β,17β-epiestriol-O-cyclic sulfone (MMSE) and a hydrolysis step. Product purification is done in the module using solid phase extraction (SPE) cartridges. The radiochemical yield was reproductive, regardless of fluor-18 activity at entry into the module, and the results of quality control tests suggest that the radiopharmaceutical meets the criteria established for other fluor-18-labelled radiopharmaceuticals that have monographs in official compendiums. In vivo biodistribution studies in healthy animals and with a tumor model developed with MCF-7 cells, demonstrated radiopharmaceutical uptake in excretory organs and specificity for breast tumor cells.